التعصب ومدى تأثيره على المستوى العلمي لطلبة المرحلة الإعدادية من وجهة نظر مديري المدارس - ساجت, احمد مطشر (Journal of College of Education, 2018)
Intolerance and its impact on the scientific level of students in the preparatory stage from the point of view of school principalsThe purpose of the research is to identify the intolerance and the extent of its impact on the scientific level of the students in the preparatory stage from the point of view of the school principals. The research consisted of (50) director and director of (56%) of the original community, 25 of them were directors, The study was based on the descriptive approach. In order to achieve the research objectives, the researchers prepared a questionnaire consisting of (25) paragraphs divided into four areas:(The field of education and behavior, the field of methods and activities, the social sphere, the use of technology for education and communication). The validity of the questionnaire was verified by presenting it to a group of experts and arbitrators. They supported the validity of the questionnaire. ) And after corrected by the equation of Sebrman Brown became a coefficient of stability (0.96) and adopted the package statistical analysis (spss) to extract the results and showed the results of the search:1 - Help the faculty to conduct dialogue dialogue with students and spirit of love,2 - The need to work to complete school curricula on decisions to renounce violence.3 - Activate the atmosphere of communication and civilizational dialogue within the school and its social environment.